Associations between glycosylated hemoglobin level at less than 24 weeks of gestation and adverse pregnancy outcomes in Japan: The Japan Environment and Children's Study (JECS). (November 2020) - Iwama, Noriyuki; Sugiyama, Takashi; Metoki, Hirohito; Saito, Masatoshi; Hoshiai, Tetsuro; Watanabe, Zen; Tanaka, Kosuke; Sasaki, Satomi; Sakurai, Kasumi; Ishikuro, Mami; Obara, Taku; Tatsuta, Nozomi; et al.
Highlights: We evaluated the associations between HbA1c levels and adverse pregnancy outcomes. The higher the HbA1c level, the higher the risk of adverse pregnancy outcomes. The HbA1c level was related to adverse pregnancy outcomes in women with HbA1c <6.5%. Abstract: Aims: To investigate the associations between glycosylated hemoglobin (HbA1c) levels at less than 24 weeks of gestation and adverse pregnancy outcomes in Japan. Methods: This was a prospective nationwide birth cohort study of 77, 526 subjects with an HbA1c level of <6.5% (<48 mmol/mol) at less than 24 weeks of gestation. Associations of HbA1c level with adverse pregnancy outcomes were evaluated using multivariate analyses. Results: The adjusted odds ratios per 1% (11 mmol/mol) increase in HbA1c level were 1.77 (95% confidence interval [CI]: 1.48–2.12) for hypertensive disorders of pregnancy; 1.78 (95% CI: 1.12–2.83) for placental abruption; 1.30 (95% CI: 1.12–1.50) for preterm birth; 2.11 (95% CI: 1.41–3.16) for very preterm birth; 1.49 (95% CI: 1.33–1.68) for low birth weight infants; 1.95 (95% CI: 1.42–2.70) for macrosomia; 1.23 (95% CI: 1.09–1.39) for small for gestational age; 1.15 (95% CI: 1.04–1.28) for large for gestational age; and 1.29 (95% CI: 1.20–1.39) for the composite adverse pregnancy outcome. Conclusions: The higher the HbA1c level, the higher the risk of adverse pregnancy outcomes in Japan. Further studies will be needed to determine prenatal management based on the HbA1c level in pregnant women with HbA1c <6.5% (<48 mmol/mol) at less than 24 weeks of gestation.